The Toys "R" Us LBO - Stowell, David P. (SAGE Knowledge. Cases., 2017)
The case simulates the experience of a private equity investor evaluating a potential investment, requiring the student to: (1) determine the risks and merits of an investment in Toys "R" Us, (2) evaluate the spectrum of returns using multiple operating model scenarios, and (3) identify strategic actions that might be undertaken to improve the risk/return profile of the investment. The case also discusses trends and participants in the private equity industry.